Jaarboek 1964 : Koninklijk Museum voor Schone Kunsten Antwerpen. - Seuphor, Michel; Koninklijk Museum voor Schone Kunsten, Antwerpen (Antwerpen : Koninklijk Museum voor Schone Kunsten, 1964)
Sonderborg, K.R.H. ; Peeters, Jozef ; Borduas, Paul-Emile ; Honegger, Gottfried ; Kline, Franz ; Bonfanti, Arturo ; Hosiasson, Philippe ; Peire, Luc ; Le Mair, J.
boek